Histomorphological study of vesiculobullous lesions of skin: a study of 66 cases at tertiary care center - Patel, Krutika; Vasudha Bhagat; Jahanvi Vyas; Prashant Patel (International Journal of Research in Medical Sciences, 2023)
Background: Wide variety of pathological processes can lead to development of vesiculobullous eruptions over the body. They may occur in many dermatoses which include various inflammatory, infective, autoimmune, drug induced as well as genetic conditions. Each entity of vesiculobullous lesion has similar or confusing clinical features but different histopathological morphology outcome. However, these disorders are still associated with substantial morbidity, considerable mortality and impaired quality of life. Histopathological examination is helpful in definitive diagnosis of vesiculobullous disorder which is very essential for specific treatment and an appropriate desirable outcome. Aim was to study and classify various vesiculobullous lesions of the skin. Methods: It was a hospital based prospective and retrospective study conducted for a period from January 2016 to July 2019 in the department of pathology at Government medical college, Surat, Gujarat. Total of 66 patients, aged 3-70 years with vesiculobullous lesions of both sexes attending the department of dermatology were selected and analysed clinically. The specimens were routinely processed and hematoxylin and eosin stained slides were studied. Results: In the present study, majority of patients presented between 41-50 years of age (32%) with male to female ratio of 1.08:1. Pemphigus vulgaris constituted the most common vesiculobullous disorder (30.30%) followed by pemphigus foliaceous (24.24%) followed by bullous pemphigoid (15.05%). Bullae were located intra epidermally in (36%+24.78%) and sub epidermally in 24% of the patients. Conclusions: Thorough histopathological workup and clinical correlation is essential to confirm diagnosis of vesiculobullous lesions of skin.